REDUCED ULCEROGENECITY FROM SELF-NANO EMULSIFYING DRUG DELIVERY SYSTEM OF PIROXICAM - Wahyuningsih,M.Si., Apt, Iis; Widyaningsih, Wahyu; Wulandari, Silviana (Pharmaciana, 2018)
Piroxicam is antiinflammatory non-steroidal (AINS) drug group that has anti-inflammatory, analgesic and antipyretic effects. Like most other AINS drugs, piroxicam has low solubility and has gastrointestinal (ulcerogenic) side effects on long-term use. The nano-emulsifying drug delivery system (SNEDDS) is one of the technologies that can be used to overcome it. This study aims to determine the effect of ulcerogenic SNEDDS piroxicam compared with piroxicam formulas instead of SNEDDS. This study uses white rats male strain SD age 2-3 months and weight 100-200 grams of 40 rats. Rats divided into 5 groups. Group I was a normal control group, the test animals were given only water. Group II was a suspending control group treated with a 1% polyvinylpyrrolidone (PVP) solution, group III is a carrier control group treated with SNEDDS carrier which is a mixture of tween 80, virgin coconut oil (VCO) and polyethylene glycol (PEG) 400, group IV was a group of piroxicam drugs suspended with piroxicam 1.08 mg/kg in 1% PVP, group V was treated with SNEDDS piroxicam.Treatment was done for 28 days. After treatment, the gastric of rats were taken to be observed for ulcerogenic effects. Observations were made macroscopically by looking at ulcer scores followed by histopathological observations of tissue. The ulcer score data from each group were analyzed using one-way ANOVAand LSD test. The results showed that the normal control group, 1% PVP suspension and carrier group had a ulcer index of 0.0, 0.0 and 0.0, while the piroxicam suspension group and the SNEDDS group had an ulcer index of 0.88 and 0.0. These results were confirmed by histopathologic results of SNEDDS piroxicam to decrease the effect of pyroxicam ulcerogenic with results in the piroxicam suspension group has ulcer with necrosis by neutrophil infiltration, lymphocytes and mast cells in the mucosal tunica to submucosa. In the SNEDDS piroxicam group there is erosion with necrosis of the mucosal tunica epithelium with infiltration of lymphocytes and mast cells in submucosal tunica. It can be concluded the SNEDDS piroxicam can decrease the ulcerogenic effect.